Konservasi Yang Hidup Dalam Ritual: Kajian Etnobiologi Upacara Kede Pada Masyarakat Adat Detupera - Pawe, Maria Serlina; Lura, Maria Magdalena Vannessa; Wae, Veronika P Sinta Mbia (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This article discusses the “Kede” traditional ceremony as a form of local wisdom-based conservation that is still preserved by the Detupera indigenous community, Ende Regency. Through an ethnobiological approach, this research examines the symbolism, ritual structure, and ecological values contained in the traditional practice. The “Kede” ceremony reflects the spiritual relationship between humans, ancestors and nature, and contains customary rules that support the sustainable preservation of natural resources. The results show that the use of local plants such as leke, denu, kela and lelu has symbolic meanings that strengthen environmental conservation and biodiversity preservation. This ritual also functions as an intergenerational ecological education system within the indigenous community. Therefore, the “Kede” ceremony can be a contextual conservation model that integrates cultural values, spirituality, and ecological ethics in maintaining the balance of nature.Kata Kunci: Konservasi, Upacara Adat, Etnobiologi, Kearifan Lokal, Ritual